P-24 A critical exploration of the questions asked and discussed by palliative care patients. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Morrison, Keith
Abstract : Background: The use of an activity with palliative care patients called 'Blether' gave us the opportunity to consider the questions asked by them in the day therapy setting. The questions proffered and discussed were collected over 20 months. There were no comparable studies found that looked at the questions palliative care patients ask or an analysis of the issues and questions that appear to be of most concern. Aim: The aim of the study was to look at any common themes that occur for the palliative care patient and which they are prepared to consider in a group setting. This knowledge is helpful to those concerned in the pastoral care of patients, be it spiritual or psychological. Methods: All of the questions proffered and discussed (as voted for by the patient group) were collected. They were categorised and then counted. They were then considered from the perspective of pastoral theology. Results: In total 367 questions were generated and of them 54 were chosen to be discussed. Upon analysis of the data we discovered that the majority of questions discussed in 'Blether' were around issues of 'meaning'. A large number of patients proffered questions about God and Faith, it was not proportionally taken up as a subject for discussion. As well as 'meaning' other high scoring categories were 'Life issues', and 'Relationships'. It is hoped that the information gained is helpful in informing the work of all practitioners concerned with the spiritual and psychological care of palliative patients. Conclusions: Issues of meaning and purpose are at the forefront of the minds of the palliative care patients and this is demonstrated when they are given the opportunity to ask a 'Spiritual' or 'Big question'. The benefits of this are that whilst anecdotal, patients appreciate this method and opportunity to stop and reflect. This work was part of an MA dissertation and has not as yet been published. 'Blether' (the activity referred to) was designed and delivered by Fire.Cloud and funded by NHS Education for Scotland.